Glyphosate Tolerant Bacteria from Rhizosphere of Kangkong (Ipomoea reptans Poir.) and Soybean (Glycine max L.) - Dina, Aslikh Lana; Solihah, Jumailatus; Khusnuryani, Arifah (Jurnal Biologi Tropis, 2025)
The use of organophosphate pesticides has some risks for human health and environment. One of the organophosphate pesticides is glyphosate. Various methods used to detoxify organophosphates including chemical methods, incineration, and landfills, produce acid and alkaline compounds, leaching pesticides around land and groundwater areas, as well as toxic emissions to the environment. The bacteria with this ability can be isolated from areas contaminated with glyphosate. Kangkong (Ipomoea reptans) and soybean (Glycine max) were chosen because of these plants are commonly found in rice fields which are areas that are frequent exposure to pesticide. The interaction between rhizosphere bacteria and plants as well as the composition of existing bacteria are closely related to the remediation occured. Kangkong and soybeans (2 weeks) were treated with glyphosate 377 mM. Soil pH was measured in third and seventh days after treat with glyphosate. The bacteria were isolated a week after treatment with glyphosate, and cultured in NA medium containing 5 mM and 10 mM glyphosate. The growing bacteria were selected and re-cultured in NA + glyphosate 10 mM medium. The selected isolates were tested for glyphosate degradation ability in Mineral Salt Media containing glyphosate 5 mM and glucose 50 mg/L. Eight isolates of bacteria grew in media containing glyphosate, i.e. Kd1, Kd2, Kd3, Kd4, Kd5 from soybeans rhizosphere, and K1, K3, K4 from spinach rhizosphere. The isolate Kd4 and K4 grew more abundantly compared the other isolates, exhibited good tolerant of glyphosate. From glyphosate degrading test, the isolate from soybean rhizosphere showed more tolerance than the isolate from kangkong rhizosphere. The molecular identification revealed that both isolates belong to species Bacillus mycoides.